Effect of resistance on 20 m running performance - Lipčák, Adam; Kalina, Tomáš (Studia sportiva, 2024)
Introduction: Sprinting is a key component in the development and final results in many individual and team sports. According to recent findings on the mechanical determinants of sprint performance, resistance sprinting (RSS) may be a suitable method to improve sprint performance in the acceleration and maximum velocity phases. Methods: Sports science students (183.6 ± 5.1 cm; 85.8 ± 6.8 kg; 24.5 ± .9 yrs), who are primarily involved in collective sports, performed two-day testing. The first testing included tests of maximal strength, isometric mid-tight pull (IMTP) and explosive lower limb strength, countermovement jump with no arm movement (CMJ). The second testing was completed 48 hours later and included unresisted sprint (URS) and resisted sprint (RSS) over 20 m with three different resistances (8 oz, 12 oz, 2 lb). Results: A significant correlation was found between CMJ and speed tests (URS, RSS 8 oz, RSS 12 oz). The same applied for the relationship with IMTP and speed tests, with only one difference being that IMTP correlated also with RSS 2 lb (r = -0.58). However, observing the relationship of velocity decrease (Vdec) and performance parameters, showed the highest correlation between Vdec 8 oz and URS 20 m (r = -0.572), and also between Vdec 12 oz and CMJ (r = -0.370). At Vdec 2 lb, of all the performance parameters, IMTP (r = -0.260) was the only one which correlated. Conclusion: The results of the study demonstrate a relationship between CMJ and IMTP with unresisted sprint. Also between maximal strength test, IMTP and heavy resisted sprint.